Taking stock of incarcerated military veterans: a review of (and guide for) research - Logan, Matthew W. (Criminal justice studies, 2023)
The sociodemographic backgrounds of inmates are essential for understanding their prison experiences and the extent to which they cope with incarceration and recidivate upon release. The notion that military veterans might fare differently from other groups in the correctional system has existed for decades; yet scholars have only recently begun to focus on the effects that prior service has on metrics of prison adjustment and beyond. Increased emphasis on the prison experiences of military veterans necessitates a review of the studies published to date. In the current study, we take stock of the empirical research conducted on incarcerated veterans by systematically reviewing all articles published online between 2000 and 2022. Overall, we find little evidence to support the view that veteran status confers any specific benefits or vulnerabilities during incarceration or following release. However, given the limitations of the studies reviewed, we address several methodological concerns regarding the study of former service members and provide directions for future research.